Anterior skull base reconstruction using nasoseptal flap: cadaveric feasibility study and clinical implication [SevEN-001] - Kyoung Su Sung; Jaejoon Lim; Minkyun Na; Sanghun Lee; Ju-Seong Kim; Je Beom Hong; Chang-Ki Hong; Ju Hyung Moon (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Pedicled nasoseptal flap (PNSF) has significantly improved the surgical outcomes of endoscopic endonasal approach (EEAs) by reducing cerebrospinal fluid (CSF) leakage. The purpose of this study is to assess the feasibility of using a PNSF for anterior skull base (ASB) reconstruction and to describe a method to compensate for a short flap based on our results. Methods In this cadaveric study, ASB dissection without sphenoidotomy was performed using 10 formalin-fixed and 5 fresh adult cadaver specimens, and the sufficiency of the PNSF to cover the ASB was assessed. After the sphenoidotomy, the length by which the PNSF fell short in providing coverage at the posterior wall of the frontal sinus (CPFS), and the extent of the anterior coverage from the limbus (CL) of the sphenoid bone was measured. Results Without sphenoidotomy, the mean length of the remaining PNSF after the coverage of the posterior wall of the frontal sinus was 0.67 cm. After sphenoidotomy, the PNSF fell short by a mean length of 2.10 cm, in providing CPFS. The CL was 1.86 cm. Based on these findings, defects resulting from an endoscopic resection of ASB tumors were reconstructed using PNSF without total sphenoidotomy in 3 patients. There were no postoperative CSF leaks or complications. Conclusions The use of PNSF for ASB reconstruction may be insufficient to cover the entire ASB defect after removal of large lesions which need total sphenoidotomy. When possible, by leaving some portion of the anterior sphenoid wall for supporting the PNSF, successful ASB reconstruction could be achieved in endoscopic resection of ASB tumors. Additional methods might be needed in some cases of large ASB lesions wherein the anterior sphenoid wall should be removed totally and the ASB defect is too large.